Avaliação da prevalência e fatores associados a lesão renal aguda em Unidade de Terapia Intensiva Pediátrica - Cibelle Ferreira Louzada (2019)
Acute Renal Injury (AKI) is a complex multi-cause disorder, with manifestations ranging from a minimal increase in serum creatinine to anuric renal failure. It is a common complication in patients admitted to the Pediatric Intensive Care Unit (PICU) and with increasing incidence, probably due to the more invasive and, consequently, more effective management of critically ill children. The present study aims to describe the AKI diagnoses available to date - Risk, injury, failure, loss and end-stage kidney disease (RIFLE), Acute Kidney Injury Network (AKIN) and Outcom Global Kidney Disease Improvement (KDIGO), discuss the pathology among the pediatric population and assess its prevalence, as well as determine the factors associated with the injury and its outcome, in a PICU. A non-systematic review of the literature on AKI was performed in critical children admitted to PICUs, and a cross-sectional observational study, including 1,131 patients admitted to the PICU between January 1, 2012 and December 31, 2016, through the evaluation of data extracted from the Work Pass. As currently validated for the diagnosis of AKI, some important advances are important, aiming at a worldwide standardization and greater agility in the recognition of diseases. The high proportion of patients with chronic disease becomes a population in this unique study. The prevalence of AKI according to the AKIN and KDIGO criteria was 12.6% and 12.9% according to pRIFLE. School age, sepsis, primary kidney disease, demand for ventilatory support and use of vasoactive amines constituted by factors associated with statistical significance to the development of AKI, corroborating the studies available in the literature. It was concluded that the identification of factors associated with AKI, as well as early diagnosis, using validated criteria and an understanding of its severity and possible consequences, are of fundamental importance for the application of preventive and therapeutic strategies. The professional working at the PICU should be aware of the maintenance of measures that ensure adequate renal perfusion in patients at risk, as well as the early diagnosis of AKI through validated diagnostic criteria. Follow-up of patients who developed AKI is imperative, considering the possibility of progression to long-term chronic kidney disease (CKD).